Body composition in sport: a comparison of a novel ultrasound imaging technique to measure subcutaneous fat tissue compared with skinfold measurement - Müller, W.; Horn, M.; Fürhapter-Rieger, A.; Kainz, P.; Kröpfl, J. M.; Maughan, R. J.; Ahammer, H. (British Journal of Sports Medicine, 2013)
Background: Extremely low weight and rapid changes in weight and body composition have become major concerns in many sports, but sufficiently accurate field methods for body composition assessment in athletes are missing. This study aimed to explore the use of ultrasound methods for assessment of body fat content in athletes.